Níveis insuficientes de atividade física : prevalência e fatores associados em escolares de um município do nordeste brasileiro - Rodrigues Munaro, Hector Luiz (Educación Física y Ciencia.)
The objective was to estimate the prevalence of insufficient levels of physical activity and associated factors in schoolchildren. The study was carried out with high school students residing in Jequié / BA, Brazil. Sample was random, proportional by conglomerates in two stages. The dependent variable was insufficient levels of activity, and the independent variables (demographic and lifestyle). Prevalence of insufficient levels of physical activity was estimated at 81.5and, after a gross and adjusted regression analysis, the variables that remained associated with insufficient levels of physical activity were: female gender, ages below 16 years old, those who did not work, those whose mothers had less than eight years old of schooling and those who had inadequate vegetable consumption. These findings support the need for school-based interventions that mainly target those subgroups that are most likely to be insufficiently active.